The Application of Audiovisual Learning Media based on Culturally Responsive Teaching to Improve Students' Learning Motivation - Nurma Mukarromah, Lingga; Kurniasih, Surti; Rozalina, Devi Putri (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2024)
Background: Each student has different characteristics, they will develop certain attitudes, interests, appreciation and goals. Therefore, the teacher's duty is to form motivation that can encourage students to do something to achieve their learning goals. This research aims to determine the effect of applying audiovisual learning media in the form of songs based on culturally responsive teaching in improving students' learning motivation on biodiversity material. Method: This research applies the collaborative classroom action reasearch methods with a quantitative approach with to sudy subjects of 36 students. The instruments used were students' initial motivational interview sheets, learning implementation observation sheets, student attitudes and skills observation sheets, and student learning motivation questionnaires. Students' learning motivation measured in this study included 10 indicators of 1) There is desire. to be successful, 2) There is encouragement and need to learn, 3) Perseverance in facing tasks, 4) Tenacity in facing difficulties, 5) Independence in acting, 6) Providing time, 7) Trying to estimate the results of various strategies, 8) Enjoying finding and solving problems - questions, 9) Courage to face failure, 10) Ability to rise from failure. Results: The results show that percentage of student motivation in cycle 1 obtained an average motivation score of 74.27%, while in cycle 2 the average percentage of student motivation was 79.57%. Overall, the average percentage of student motivation in cycles 1 and 2 was 76.92%. Conclusion: The implementation of audiovisual learning media in the form of CRT-based songs in biodiversity material can improve students' learning motivation. This can be seen from the average percentage of students' learning motivation of 76.92% with moderate motivation interpretatios. Keywords : Classroom Action Research; Motivation; Audiovisual Media; Learning Songs; Culturally Responsive Teaching; Biodiversity